Autonomia dos Estados em caso de ausência de lei complementar tributária para evitar conflitos de competência um estudo à luz do federalismo - Vasconcelos, Sergio Villanova Mozdzenski de Lemos (2023)
The purpose of this paper is to analyze, in the absence of a supplementary tax law, what are the limits of the legislative autonomy of the States and the Federal District in the exercise of their tax competence to institute and collect taxes, under the terms of art. 155, of the Federal Constitution of 1988. The examination was based on the study of federalism, with an indication of the main characteristics of this form of State, in particular regarding the autonomy of the federated units and the necessary harmony that must exist in the federal system. In this context, the technique of division of legislative competence among the federative units provided by the Federal Constitution of 1988 was analyzed in this paper, with a greater focus on fields of concurrent competence, as is the case of tax law, under the terms of item I, of art. 24, of the Constitution. In this case, the need for a national law with general rules to deal with issues that could affect federative harmony was exposed. In this sense, it was indicated that the competent law to deal with issues that can impact the interrelationship between the States and the Federal District is the supplementary tax law. With this premise, the States and the Federal District may enact a legislation on this subject only if Congress enacts a supplementary law